Fostering a safe psychological environment and encouraging speak-up culture in primary care setups - Awar, Dina T. A.; Abdulla, Fatima I. M.; Bakhamis, Sarah Ahmad A.; Rashid, Maryam A. A.; Saleh, A. Anoud; Mamalac, Aida D.; Laja, Nurdini (International Journal of Research in Medical Sciences, 2023)
Patient safety is a critical concern in healthcare, and encouraging healthcare employees to speak up and voice their concerns plays a pivotal role in preventing avoidable harm to patients. Establishing a safe environment and fostering a supportive psychological climate within healthcare organizations, particularly in primary care settings, is essential for achieving better patient outcomes and enhancing overall organizational performance. This review emphasizes the importance of a safe environment and supportive psychological climate in primary care, enhancing patient outcomes and organizational performance. Speaking up leads to timely error correction, mitigates unsafe practices, and upholds ethical standards despite barriers like hierarchy, fear of retaliation, and inadequate policies. In the quest to foster a culture of speaking up, diverse interventions have emerged, ranging from comprehensive training initiatives to initiatives promoting psychological safety and establishing clear communication channels. Leadership development programs play a vital role in encouraging employee voices and fostering a positive environment for open communication. To advance further, research must evaluate intervention impact and contextual nuances for more tailored strategies. In conclusion, psychological safety is vital for speaking up and enhancing employee engagement, communication, and patient outcomes. Overcoming implementation challenges and fostering a culture of safety and open communication empower healthcare employees to contribute to continuous improvement in patient care. Leadership development plays a pivotal role in nurturing this culture envisioning a safer, compassionate healthcare ecosystem.